Prince, Pen, and Sword: Eurasian Perspectives - van Berkel, Maaike (Rulers & Elites, 2018)
A synoptic interpretation of the rulers and elites in Eurasia from the fourteenth to the eighteenth century. Readership: All interested in the early modern global and comparative history of kingdoms and empires, rulers and elites, including area specialists as well as generalists. This book is intended for students and scholars.